Diva reduces cell death in response to oxidative stress and cytotoxicity. - Nicole Suyun Liu; Xiaoli Du; Jia Lu; Bei Ping He (PLoS ONE, 2012)
Diva is a member of the Bcl2 family but its function in apoptosis remains largely unclear because of its specific expression found within limited adult tissues. Previous overexpression studies done on various cell lines yielded conflicting conclusions pertaining to its apoptotic function. Here, we discovered the expression of endogenous Diva in PC12 neuronal-like cell line and rat bone marrow mesenchymal stem cells (BMSCs), leading to their utilisation for the functional study of Diva. Through usage of recombinant Fas ligand, hydrogen peroxide, overexpression and knock down experiments, we discovered that Diva plays a crucial pro-survival role via the mitochondrial death pathway. In addition, immunoprecipitation studies also noted a decrease in Diva's interaction with Bcl2 and Bax following apoptosis induced by oxidative stress. By overexpressing Diva in BMSCs, we had observed an increase in the cells' capacity to survive under oxidative stress and microglial toxicity. The result obtained from our study gives us reason to believe that Diva plays an important role in controlling the survival of BMSCs. Through overexpression of Diva, the viability of these BMSCs may be boosted under adverse conditions.